2018
DOI: 10.1002/pbc.27027
|View full text |Cite
|
Sign up to set email alerts
|

Parent pain catastrophizing predicts child depressive symptoms in youth with sickle cell disease

Abstract: Findings support the value of depression screening and interventions to promote parent self-efficacy in managing childhood SCD pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…32 Parent catastrophizing may influence the pain experience of children with SCD 33 and significantly contribute to their depressive symptoms. 34,35 These studies highlight the bidirectional link between mental illness and pain, with both conditions mutually reinforcing one another.…”
Section: Psychiatric Disorders and Chronic Painmentioning
confidence: 92%
“…32 Parent catastrophizing may influence the pain experience of children with SCD 33 and significantly contribute to their depressive symptoms. 34,35 These studies highlight the bidirectional link between mental illness and pain, with both conditions mutually reinforcing one another.…”
Section: Psychiatric Disorders and Chronic Painmentioning
confidence: 92%
“…Across studies that examined the relationship between pain and depressive symptoms, there was significant variability in levels of depressive symptoms. For studies examining pain frequency, intensity, or pain coping, the percentage of youth with clinically significant cut-off scores on depressive measures ranged from 4 to 27% (Barakat, Schwartz, Simon, & Radcliffe, 2007;Goldstein-Leever, Cohen, Dampier, & Sil, 2018;Hoff, Palermo, Schluchter, Zebracki, & Drotar, 2006;Palermo, Platt-Houston, Kiska, & Berman, 2005).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Data reported by patients are important data to collect in patients with SCD. Indeed, patients’ poor perception of quality of life can lead to depressive symptoms, which are themselves risk factors, particularly in children, for chronic pain [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein-Leever et al have shown a link between parents’ perception of pain and children’s perception of pain in SCD. Parents’ catastrophizing about their child’s pain contributed to child’s depressive symptoms, symptoms that have been identified as risk factors for chronic SCD pain [ 41 ]. Parental health and parenting beliefs and behaviours are known to have a significant impact on child pain management, and parental emotional distress and depression represent an independent risk factor for adverse child outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation